Kinetic investigations into the possible cause of low serum histidine in rheumatoid arthritis. - Sitton, N G (1988)
To investigate the cause of low serum histidine in rheumatoid arthritis (RA) single oral and intravenous doses of L-histidine were administered to patients with active RA, and to an equal number of age and sex matched control subjects. In the first study 13 patients and their controls received a 100 mg kg-1 dose of L-histidine as an aqueous slurry. Significant differences were seen in body weight, predose baseline serum histidine concentration, Cmax, t1/2, and area under curve, AUC0-infinity. In a second study six patients and six controls each received a 50 mg kg-1 dose of L-histidine both orally and intravenously on two separate occasions. The patients with RA had a lower baseline serum histidine concentration, a lower volume of distribution, and a shorter plasma half life than the controls, but these differences were not statistically significant. No difference was seen in bioavailability or clearance. Low serum histidine in RA is unlikely to be due to malabsorption from the gut, uptake by abnormal gut flora, or increased metabolism.